2016
DOI: 10.18632/oncotarget.13535
|View full text |Cite
|
Sign up to set email alerts
|

Activation of endoplasmic reticulum stress and the extrinsic apoptotic pathway in human lung cancer cells by the new synthetic flavonoid, LZ-205

Abstract: It has been shown that flavonoids have anti-tumor activity. In this study, LZ-205, a newly synthesized flavonoid, was found to be effective in inducing apoptosis in human lung cancer cells in vivo and in vitro. Mechanistically, LZ-205 triggers reactive oxygen species (ROS)-induced endoplasmic reticulum (ER) stress and unfolded protein response, which could be reversed by silencing CHOP, a mediator of the ER stress-associated apoptosis. In addition, LZ-205-induced apoptosis is accompanied by the activation of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Targeting ER stress can be a useful anti-cancer strategy. Recently, it was reported that some compounds exerts its proapoptotic effects by inducing ER stress in H460 and A549 cells [ 30 , 31 , 32 ]. In the present study, we observed an increasing of ER stress-related proteins such as ATF4 and p-EIF2α in a time- and dose-dependent manner, indicating that ER stress was activated after LicA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting ER stress can be a useful anti-cancer strategy. Recently, it was reported that some compounds exerts its proapoptotic effects by inducing ER stress in H460 and A549 cells [ 30 , 31 , 32 ]. In the present study, we observed an increasing of ER stress-related proteins such as ATF4 and p-EIF2α in a time- and dose-dependent manner, indicating that ER stress was activated after LicA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar cell apoptosis is a critical step in the pathogenesis of emphysema [ 36 , 37 ]. ER stress has been implicated in apoptotic signaling [ 7 ] and has been shown to regulate apoptosis in lung epithelial cells and human lung cancer cells [ 38 40 ]. Our results are in agreement with these studies in that downregulation of ER stress by 4-PBA decreased CS-induced cell apoptosis, thus preserving alveolar structure.…”
Section: Discussionmentioning
confidence: 99%
“…A persistent and overwhelming ER stress will lead to apoptosis. Several studies have reported that tocotrienols exert ER stress as one of the mechanisms to induce apoptosis [65,66,67]. In this section, the evidences of tocotrienols-induced ER stress are gathered and aligned to the present understanding on apoptosis that is led by ER stress (Figure 4).…”
Section: Tocotrienols Act As a Potent Apoptosis Inducermentioning
confidence: 86%